Monumental lies : culture wars and the truth about the past - Bevan, Robert (Journalist) (London ; New York : Verso, 2022)
How statues, heritage and the built environment have become the battleground for the culture wars. The past is weaponized in culture wars and cynically edited by those who wish to impose their ideology upon the physical spaces around us. Holocaust deniers use details of the ruins of the gas chambers Auschwitz to promote their lies: 'No Holes; No Holocaust'. Yet long-standing concepts such as 'authenticity' in heritage are undermined and trivialized by gatekeepers such as UNESCO. At the same, time, opposition to this manipulation is being undermined by cultural ideas that prioritise memory and impressions over history and facts.In Monumental Lies, Robert Bevan argues that monuments, architecture and cities are material evidence of history. They are the physical trace of past events, of previous ways of thinking and of politics, economics and values that percolate through to today. When our cities are reshaped as fantasies about the past, when monuments tell lies about who deserves honour or are destroyed and the struggle for justice forgotten, the historical record is being manipulated. When decisions are based on misinformed assumptions about how the built environment influences our behaviour or we are told, falsely, that certain architectural styles are alien to our cities, or when space pretends to be public but is private, or that physical separation is natural, we are being manipulated. There is a growing threat to the material evidence of the truth about history.We are in serious trouble if we can no longer trust the tangible world around us to tell us the truth. Monumental Lies explores the threats to our understanding of the built environment and how it impacts on our lives, as well as offers solutions to how to combat the ideological manipulations. --
Includes bibliographical references and index.
Keywords: Monuments -- Social aspects; Cultural property -- Political aspects; Collective memory; Politics and culture